2020
DOI: 10.1155/2020/7863709
|View full text |Cite
|
Sign up to set email alerts
|

Galactosamine-Conjugating Zwitterionic Block Copolymer for Reduction-Responsive Release and Active Targeted Delivery of Doxorubicin to Hepatic Carcinoma Cells

Abstract: Nanocarriers with integrated advantage, such as excellent stealth property, active targeting function, and rapid intracellular drug release, are significant for cancer treatment. Herein, a biodegradable zwitterionic triblock copolymer containing disulfide-linked poly-ε-caprolactone and polycarboxybetaine methacrylate (PCB-SS-PCL-SS-PCB) was first synthesized and then partly modified with galactosamine (GAL) for constructing polymeric micelle drug carrier with multifunctionality. Polymeric micelles showed ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Several studies have shown that liver cells can target liposomes by recognizing and taking up liposomes. For example, receptors such as the low-density lipoprotein receptor (LDLR) [90] and transferrin receptor (TfR) [178] can interact with liposomes and participate in their mechanism of targeting diseased areas of the liver.…”
Section: Active Targetingmentioning
confidence: 99%
“…Several studies have shown that liver cells can target liposomes by recognizing and taking up liposomes. For example, receptors such as the low-density lipoprotein receptor (LDLR) [90] and transferrin receptor (TfR) [178] can interact with liposomes and participate in their mechanism of targeting diseased areas of the liver.…”
Section: Active Targetingmentioning
confidence: 99%